A Minimalist analysis of Uyghur genitives - Politzer-Ahles, Stephen (Kansas Working Papers in Linguistics, 2011)
This paper investigates the syntactic structure of so-called genitive-possessive DPs in Uyghur, a Turkic language. Uyghur genitive-possessives bear suffixes on both the “possessing” entity (comparable to the Saxon genitive ’s in English) and the “possessed” one. The suffix on the “possessor”, -ning, is considered a genitive case marker; the suffix on the “possessed” has multiple allomorphs and is considered an agreement marker that agrees in person and number with the “possessor”. Based on the multiplicity of semantic roles that the “possessing” object may bear, and the observation that it may be dropped from the DP, an analogy is made between genitive-possessive DPs and finite TPs. It is proposed that “possessors” behave in a manner parallel to that of subjects of TPs: they are introduced by a quasi-functional head n or within a gerund, and raise to [Spec,DP] to receive genitive case from D. The agreement suffix, on the other hand, is treated as the phonological realization of an Agr head that is introduced with unvalued phi-features, features which are valued when the “possessing” entity passes through the specifier of AgrP. Adopting this structure can explain data on the realization of definiteness in genitive and non-genitive DPs, and the distribution of adverbials within gerunds.